Dental Staff Practices and Awareness of Microbiological Contamination of Water in Dental Units in Tripoli, Libya - Eman Muftah Elzouki; Najah Ahmeda Ibrahim; Ashraf Saad Elzer (African Journal of Advanced Pure and Applied Sciences, 2023)
Objective: This study aimed to evaluate awareness of dentists of microbiological contamination in Dental Units (DUs). Methods: Cross-section survey was carrying out in nine government hospitals and three privates’ dental clinics in a Tripoli city of Libya. Data was gathered over a 16-months period (from April 2021 to end of July 2022) using an especially designed survey. SPSS software was used for data analysis and the appropriate statistical tests were applied at (p value set at 0.05). Results: A total of the 204 surveyed dentists, 116 (56.7%) were females and 88 (43.3%) were males. They age between 26 - 57 years. It was pointed out that all of the enrolled dentists (100.0%) had knowledge about the causes of contamination of dental chair units (DCUs). Moreover, it was found that the majority of them did not perform the following practices: allowing water to flow out of the air/water syringes, allowing water to flow outside handpieces, covering light handles with disposable plastic sheets, covering head cushions with disposable plastic sheets, changing medical masks after each patient, wearing protective glasses, and disinfecting protective glasses after each patient, (90.2%, 88.2%, 89.7%, 90.2%, 88.2%, 89.2%, 88.7%, respectively).Conclusions: It can be concluded from this study that: dentists had adequate knowledge about the causes of contamination of dental chair units (DCUs) and mean to prevent them. Yet their practices were found to be suboptimal.